Effect of aerobic training and resistance training on circulating irisin level and their association with change of body composition in overweight/obese adults: a pilot study - Kim, H-J; Lee, H-J; So, B; Son, J S; Yoon, D; Song, W (Physiological research, 2016)
The novel myokine irisin has been reported as a therapeutic target for metabolic disease. The objective of this study is to reveal the effects of aerobic training (AT) and resistance training (RT) on circulating irisin levels and their associations with change of body composition in overweight/obese adults. Twenty eight overweight/obese adults (BMI>23 kg/m(2)) were included in this study and compared before and after 8 weeks of exercise program (60 min/day, 5 times in a week). The subjects, in both aerobic and resistance training, showed significant improvement in anthropometric parameters and exercise capacities including maximal oxygen uptake and muscle strength. Interestingly, the circulating irisin was significantly increased in resistance training group (p=0.002) but not in aerobic training (p=0.426) compared to control group. In addition, we found the positive correlation between change of the circulating irisin and muscle mass (r=0.432, p=0.022) and the negative correlation between change of the circulating irisin and fat mass (r=-0.407, p=0.031). In the present pilot study, we found that circulating irisin level was increased by 8 weeks of resistance training in overweight/obese adults, suggesting that resistance training could be the efficient exercise type in overweight/obese considering positive change of body composition concomitant with increase of irisin levels.
Keywords: Resistance Training; Obesity; cvičení; výsledek terapie; fibronektiny; mužské pohlaví; Adult; Overweight; složení těla; odporový trénink; ženské pohlaví; Fibronectins; Humans; biologické markery; pilotní projekty; obezita; nadváha; Pilot Projects; Exercise; Body Composition; dospělí; Biomarkers; Female; Treatment Outcome; lidé; Male